Effective Recruitment or Bot Attack? The Challenge of Internet-Based Research Surveys and Recommendations to Reduce Risk and Improve Robustness - Donkin, Liesje; Henry, Nathan; Kercher, Amy; Pedersen, Mangor; Wilson, Holly; Chan, Amy Hai Yan (JMIR Publications Inc., 2024)
Internet-based research has exploded in popularity in recent years, enabling researchers to offer both investigations and interventions to broader participant populations than ever before. However, challenges associated with internet-based research have also increased-notably, difficulties verifying participant data and deliberate data manipulation by bot and spam responses. This study presents a viewpoint based on 2 case studies where internet-based research was affected by bot and spam attacks. We aim to share the learnings from these experiences with recommendations for future research practice that may reduce the likelihood or impact of future attacks. The screening and verification processes used are presented and discussed, including the limitations of these. Based on our experience, security and screening within internet-based research platforms are partly effective, but no solution is available to protect researchers completely against bot attacks. Implications for future research and advice for health researchers are discussed.
Keywords: bot attacks; bots; data collection; data integrity; data manipulation; false; falsification; fraud; fraudulent; internet-based research; participants; research methodology; research methods; spam; surveys; technology; verification; verify; 32 Biomedical and Clinical Sciences; 42 Health Sciences; 1103 Clinical Sciences